Ownership and occupation contestations in South Africa: the case of state housing in Buffalo City Municipality, Eastern Cape - Msindo, Esteri Makotore (Rhodes University, Faculty of Humanities, Department of Sociology)
This thesis examines contestations around access to state-provided housing or simply state housing in South Africa, using a case study of two sites in Buffalo City Municipality, and with a particular focus on occupation without ownership through informal and illegal means. While the South African state, based on an official human rights discourse and regime, seeks to provide state housing to the urban poor, massive housing backlogs continue to exist within urban spaces. As a result, the urban poor turn to self-provisioning through the construction of informal settlements or backyard shacks, waiting at times indefinitely to be allocated a state house via the official housing waiting lists. To overcome this problem, some amongst the urban poor opt to circumvent the process by invading and illegally occupying state houses, leading to occupation without ownership. In doing so, they draw upon their own moral rights-claims to justify their actions. The thesis examines the multiple causes for occupation and ownership contestations in the two research sites as well as the different forms that these contestations take. The study is framed theoretically in terms of a sociology of human rights, identifying and analysing how moral claims to rights amongst ordinary people often come into conflict with a legal-institutional conception of rights adopted by the state. The study also draws on a diverse array of theorists whose work speaks to the manner in which ordinary citizens develop their own ways of acting contrary to state officialdom. Using interpretive sociology, the study considers the views and practices of those illegally occupying houses without ownership and those who feel victimised by these informal actions. It considers these intra-community dynamics in light of the machinations of local state powerholders at municipal level. As with interpretive sociology, then, the thesis privileges social realms of meanings, interpretations, experiences and practices of human agents. Informal state housing occupations in the Buffalo City Municipality are caused by a number of factors related to state incapacity, weak policies and poor planning, corruption, resource constraints and so on. The study vividly demonstrates the tensions arising and existing between the South African state's legal human rights regime and locally-constructed moral-rights regimes amongst the urban poor. This tension is seen in the interrelated phenomena of 'occupation without ownership' and 'ownership without occupation', as the poor draw upon and use ordinary logics of rights for recourse. The thesis shows how diverse rights regimes lead to intra-community conflict, in particular along generational and racial lines.
Keywords: Public housing -- South Africa Buffalo City; Squatters -- South Africa Buffalo City; Occupancy (Law) -- South Africa; Acquisition of property -- South Africa Buffalo City; Right of property -- South Africa Buffalo City; Sociology, Urban -- South Africa Buffalo City; Marginality, Social -- South Africa Buffalo City; Human rights -- South Africa; Acquisition of property Moral and ethical aspects -- South Africa Buffalo City; Urban poor -- South Africa Buffalo City Social conditions